2021
DOI: 10.3390/plants10102047
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat (Triticum aestivum L.) Tolerance to Mulch

Abstract: Mulch from cover crops can effectively suppress weeds in organic corn (Zea mays L.) and soybean (Glycine max L.) as part of cover crop-based rotational no-till systems, but little is known about the feasibility of using mulch to suppress weeds in organic winter small grain crops. A field experiment was conducted in central NY, USA, to quantify winter wheat (Triticum aestivum L.) seedling emergence, weed and crop biomass production, and wheat grain yield across a gradient of mulch biomass. Winter wheat seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Soybean was planted with a four-row (76-cm width) John Deere ® 1755 planter (John Deere) as part of single-pass operation at rolling in fields with cereal rye (Fields 1a, 1b, and 2a) (Table 1). The planter was modified for no-till planting into cover crop mulch, with hydraulic downforce, double disk openers before the planting tube, a seed-firmer behind the seed tube, and cast-iron notched closing wheels (Ryan et al 2021). Fields without cereal rye (Fields 1c and 2b) were disked and cultimulched before soybean planting, but no secondary cultivation (i.e., tine weeding, rotary hoeing, or interrow cultivation) was used after soybean establishment (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Soybean was planted with a four-row (76-cm width) John Deere ® 1755 planter (John Deere) as part of single-pass operation at rolling in fields with cereal rye (Fields 1a, 1b, and 2a) (Table 1). The planter was modified for no-till planting into cover crop mulch, with hydraulic downforce, double disk openers before the planting tube, a seed-firmer behind the seed tube, and cast-iron notched closing wheels (Ryan et al 2021). Fields without cereal rye (Fields 1c and 2b) were disked and cultimulched before soybean planting, but no secondary cultivation (i.e., tine weeding, rotary hoeing, or interrow cultivation) was used after soybean establishment (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has focused on several aspects of cereal rye management, including planting and termination dates, seeding rates, cultivar selection, and fertilizer application (Crowley et al 2018; Mirsky et al 2009, 2011, 2013; Ryan et al 2011a, 2021; Teasdale and Mohler 2000; Wells et al 2016). Studies that evaluated fall-planting dates found that planting cereal rye in late August to early September allows the crop to reach optimal biomass for weed suppression (more than 8,000 to 9,000 kg ha– 1 ) at time of roller-crimping (Mirsky et al 2009, 2011; Ryan et al 2021; Teasdale and Mohler 2000). In addition, seeding cereal rye between 135 to 269 kg ha– 1 , depending on planting date and location, can provide a thick stand in the spring, leading to cereal rye competition with early-emerging weeds and reduced weed biomass (Mirsky et al 2013; Ryan et al 2011a, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that the use of sage (Salvia officinalis L.) and lemongrass (Cymbopogon citratus (DC) Stapf) as living mulches combined to minimize soil disturbance, reduce the need for weed management, and promote the complexity of the Arthropod fauna in terms of both the number of species and the taxonomic complexity. Another technique related to cover cropping, i.e., mulching, was studied in this Special Issue by Ryan et al [8] in winter wheat cultivated in central New York (USA). Evaluating a gradient of mulch biomass primarily composed of perennial species such as orchardgrass (Dactylis glomerata L.), timothy (Phleum pratense L.) and red clover (T. pratense), they found that wheat seedling density showed an asymptotic relationship with mulch biomass (no effect at low rates and a gradual decrease from moderate-to-high rates of mulch) and that the highest level of mulch (9000 kg ha −1 ) selectively suppressed weed biomass without reducing wheat grain yield.…”
Section: Cover Croppingmentioning
confidence: 99%